Community Participation in the Implementation of Development in the Panamas Village, Selat District, Kapuas Regency - Yaya Setiabudi; Irawanto; Semuel Risal (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research focuses on community participation in implementing development in the Panamas Village, Selat District, Kapuas Regency. This study is designed to measure the level of participation, understand the factors that encourage and inhibit participation, and provide recommendations for increasing community involvement in development. The research methodology was carried out through in-depth interviews and focus group discussions with various stakeholders. The research results show that the level of community participation in the development process still varies, with some segments of society being more active than others. Factors influencing this include knowledge of the development project, access to information, trust in local government, and capacity to participate. The study notes that increased communication and transparency, as well as community empowerment through education and training, can be effective strategies to deepen community participation. The results of this study are expected to contribute to the local government and civil society organizations in efforts to increase community participation in development in the Panamas Village.